The Fallacy of Univariate Solutions to Complex Systems Problems - Lessov-Schlaggar, Christina N.; Rubin, Joshua B.; Schlaggar, Bradley L. (Frontiers in Neuroscience, 2016)
Complex biological systems, by definition, are composed of multiple components that interact non-linearly. The human brain constitutes, arguably, the most complex biological system known. Yet most investigation of the brain and its function is carried out using assumptions appropriate for simple systems – univariate design and linear statistical approaches. This heuristic must change before we can hope to discover and test interventions to improve the lives of individuals with complex disorders of brain development and function. Indeed, a movement away from simplistic models of biological systems will benefit essentially all domains of biology and medicine. The present brief essay lays the foundation for this argument.